2003
DOI: 10.1021/ja036021l
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regio- and Stereoselective Acylboration, Acylsilation, and Acylstannation of Allenes Catalyzed by Phosphine-Free Palladium Complexes:  An Efficient Route to a New Class of 2-Acylallylmetal Reagents

Abstract: A new method for the synthesis of substituted 2-acylallylmetal reagents in a highly regio- and stereoselective fashion involving a three-component assembly of allenes, acyl chlorides, and bimetallic reagents (B-B, Si-Si, and Sn-Sn) catalyzed by phosphine-free palladium complexes is described. Treatment of various allenes (CR(2)R(3)=C=CH(2)) with acyl chlorides (R(1)COCl) and bispinacolatodiboron in the presence of PdCl(2)(CH(3)CN)(2) in toluene at 80 degrees C gave 2-acylallylboronates in moderate to good yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 83 publications
1
26
0
1
Order By: Relevance
“…Cheng has demonstrated that phosphine-free Pd complexes together with alkenyl or aryl iodides are very efficient catalysts for 1,2-diboration of allenes. 67,68 This reaction is completely regioselective and highly stereoselective affording diborated products with mainly Z stereochemistry. This Pd-catalyzed reaction proceeds via a previously unknown mechanism involving the oxidative addition of an IdB bond into the palladium center instead of the oxidative addition of a BdB bond to metal (Scheme 18).…”
Section: Activation By Metal Complexes Of Group 10mentioning
confidence: 99%
“…Cheng has demonstrated that phosphine-free Pd complexes together with alkenyl or aryl iodides are very efficient catalysts for 1,2-diboration of allenes. 67,68 This reaction is completely regioselective and highly stereoselective affording diborated products with mainly Z stereochemistry. This Pd-catalyzed reaction proceeds via a previously unknown mechanism involving the oxidative addition of an IdB bond into the palladium center instead of the oxidative addition of a BdB bond to metal (Scheme 18).…”
Section: Activation By Metal Complexes Of Group 10mentioning
confidence: 99%
“…In recent years, similar strategies were developed by Cheng and co-workers to prepare allyl azides [63] and allylic silanes [64]. The same group developed efficient palladium-mediated methods [65] for the assembling of acyl chlorides, allenes, N I 9 5 mol% Pd(dba) 2 and bimetallic reagents such as bis(pinacolato)diboron, hexamethyldisilane, and hexabutylditin to form the corresponding 2-acylallylmetal reagents (Scheme 8.24). Related acylation of allenes using acyltetracarbonylcobalt complexes and subsequent intermolecular nucleophilic attack of the resulting p-allyl complexes by alkylnitronates had been developed previously by Hegedus [66].…”
Section: Carbopalladation Of Allenesmentioning
confidence: 99%
“…Keywords: carbometalation · cross-coupling · nickel · organoboronic acids · trans-addition [11] Herein, we describe the detail of our findings on nickelcatalyzed cyclizative carboboration of chloroboryl ethers of homopropargyl and bishomopropargyl alcohols by using organometallic reagents as donors of organic groups. A preliminary report on this topic appeared previously on the use of alkynylstannanes as the transmetalation reagent.…”
Section: Introductionmentioning
confidence: 99%